Transformation Of Shopping Culture And Negotiation Of Consumer Decisions In Tamanan District - Deviyatul Hasanah; Haqiqotus Sa’adah (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study aims to analyze the impact of the presence of modern markets on the marketing performance of traditional markets from the perspectives of traders and consumers in Tamanan Regency. This research employs a descriptive qualitative approach, with data collected through interviews. The sampling technique used is non-probability sampling (purposive sampling), and data analysis is conducted by organizing data into categories, describing them into units, synthesizing, arranging them into patterns, selecting important aspects to be studied, and drawing conclusions. The results indicate that the presence of modern markets in Tamanan Regency has both positive and negative impacts. Traditional market traders experience a decline in profits and market share due to market segmentation; however, traders also recognize that changes over time and regional development necessitate adaptation and renewal of business systems to minimize competition and enhance partnerships as well as competitiveness within the industry. The Tamanan Regency Government is expected to acknowledge this condition and formulate policies to regulate the operational systems of both traditional and modern markets, enabling them to operate more dynamically and coexist without engaging in price wars that could negatively affect the market ecosystem or price stability